The global implications of US EMV adoption. (February 2016) - Froud, David
Abstract : There was a significant event in global card payments on 1 Oct 2015, as it was the date of the EMV liability shift in the US. EMV stands for Europay, MasterCard and Visa, the three companies that originally created the standard and it is often referred to as Chip and PIN. The US is finally adopting EMV security for payment cards, although not in its most secure form. However, this may do little to stem one of the biggest problems facing the payment card industry – card not present (CNP) fraud. Thanks to e-commerce, this has emerged as the most prevalent kind of card fraud and one that EMV does little to tackle. And the way that the US is adopting EMV – still using signatures for authentication – could mean that the country's merchants and payment processors may get only a modest return for the major investment involved, as David Froud of myPINpad explains.